Effects of spray parameters on skin tumour ablation volume during cryotherapy - Kumari C.; Kumar A.; Sarangi S.K.; Thirugnanam A. (My University, 2025)
The main purpose of the study is to establish correlations for the ablation volume and the ice front as a function of the spray parameters. The ablation volume and the ice front depend upon the nozzle diameter, spraying distance and the freeze duration (spray parameters). The estimation of the ablation volume using the spray parameters shall be useful in surgical practice to ablate the different sizes of tumours. Liquid nitrogen spray cooling is carried out with 0.8 mm, 0.6 mm and 0.4 mm nozzle diameters. The spraying distance is maintained at 9 mm, 18 mm and 27 mm. The spray cooling is carried out for a single freeze–thaw cycle where freezing and thawing consist of 120 s and 130 s duration respectively. A two-dimensional heat flow equation with phase change is considered for the numerical study. The numerically calculated transient temperature (2 mm and 5 mm from the gel surface) and ice front values show confirmatory results with the experimentally measured data. Correlations are obtained to determine the ablation volume (− 50 °C and − 25 °C isothermal surfaces) and ice front (axial and lateral) with a goodness of fit ≥ 95%. The nozzle diameter has a greater impact on the ablation volume as compared to the spraying distance during 120 s of freezing. The nozzle diameter of 0.8 mm, 0.6 mm and 0.4 mm can be effectively used for cryotherapy with spraying distance up to 27 mm, 18 mm and 9 mm respectively. © 2019, Australasian College of Physical Scientists and Engineers in Medicine.